Kinetika vulkanisasi campuran NR/EPDM dengan pendekatan model Deng-Isayev dan Kamal-Sorour - Ihda Novia Indrajati; Muhammad Sholeh (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2014)
Curing kinetics of natural rubber/ethylene propylene diene monomer (NR/EPDM) blends at different ratios of 2,2’-dithiobis(benzothiazole) (MBTS) and zinc diethyl dithiocarbamate (ZDEC) were studied. NR/EPDM blends were prepared using curative migration control technique. Kinetics studies employ Deng-Isayev and Kamal-Sorour models and kinetics parameters were evaluated using measured data from Moving Die Rheometer. Rate constant (k) and orders of reaction (n and m) were estimated through multivariable optimization using Matlab and activation energy (E) was determined using Arrhenius relationship. From the results, it is evident that the experimental data were in a good agreement with Kamal-Sorour model. It is also found that autocatalytic mechanism was more controlling than the others as indicated by k2>k1. Results also shows that rate constants were greatly influenced by temperature and the types of accelerator, while orders of reaction were dependent on temperature and independent on the types and amounts of accelerator. Combination of MBTS and ZDEC reduces energy activation of autocatalytic reaction. For desirable rate of curing, its ratio of 1.4 to 0.2 gave the lowest activation energy.Keywords: kinetics study, vulcanization, NR/EPDM, Deng-Isayev, Kamal-Sorour.ABSTRAKKinetika vulkanisasi campuran NR/EPDM pada berbagai rasio MBTS/ZDEC dipelajari dalam publikasi ini berdasarkan data output Moving Die Rheometer (MDR). Campuran NR/EPDM dibuat dengan teknik kontrol migrasi curatives. Pendekatan yang digunakan adalah model empiris Deng-Isayev dan Kamal-Sorour. Konstanta kecepatan reaksi (k) dan orde reaksi (n dan m) ditentukan dengan optimasi multivariabel menggunakan perangkat lunak Matlab. Energi aktivasi (E) ditentukan dengan hubungan Arrhenius. Hasil studi menunjukkan data eksperimen dapat dideskripsikan dengan baik oleh model Kamal-Sorour. Mekanisme autokatalitik mendominasi mekanisme lainnya ditunjukkan dengan k2>k1. Konstanta kecepatan reaksi bergantung pada suhu dan jenis akselerator, sedangkan orde reaksi tidak tergantung pada suhu tetapi pada jenis dan jumlah akselerator. Kombinasi akselerator MBTS dan ZDEC menurunkan energi aktivasi reaksi autokatalisis. Rasio 1,4/0,2 merupakan kombinasi yang memberikan energi aktivasi cukup rendah dengan kecepatan reaksi yang tinggi.Kata kunci: kinetika, vulkanisasi, NR/EPDM, Deng-Isayev, Kamal-Sorour.